Impact of NAFTA on labor arbitration in Mexico. - RUHNKE, Jill Sauner (1995)
Explores the competing pressures created by NAFTA on the Mexican system of labor arbitration. Assesses the likelihood that NAFTA will result in the xport of US arbitration procedures to Mexico.